2007
DOI: 10.1007/s10641-007-9202-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of visual survey and seining methods for estimating abundance of an endangered, benthic stream fish

Abstract: We compared visual survey and seining methods for estimating abundance of endangered Okaloosa darters, Etheostoma okaloosae, in 12 replicate stream reaches during August 2001. For each 20-m stream reach, two divers systematically located and marked the position of darters and then a second crew of three to five people came through with a small-mesh seine and exhaustively sampled the same area. Visual surveys required little extra time to complete. Visual counts (24.2 ± 12.0; mean ± one SD) considerably exceede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…In particular, underwater video systems are becoming increasingly popular for studying fishes in marine [7], [8], estuarine [9], [10], [11] and freshwater habitats [12], [13]. They are especially desirable when a key objective is to minimize or avoid the adverse effects of handling stress associated with traditional sampling methods [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, underwater video systems are becoming increasingly popular for studying fishes in marine [7], [8], estuarine [9], [10], [11] and freshwater habitats [12], [13]. They are especially desirable when a key objective is to minimize or avoid the adverse effects of handling stress associated with traditional sampling methods [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…Our study indicated that the relative effectiveness of these two methods differed among species and that snorkel sampling was comparable or in some cases superior to electrofi shing for estimating site occupancy. Jordan et al (2008) found that snorkel sampling was more accurate and precise than seining for estimating the abundance of Etheostoma okaloosae (Fowler) Okaloosa Darter. Thurow et al (2006) documented higher detection rates for single-pass backpack electrofi shing compared to daytime snorkeling for Salvelinus confl uentis (Suckley) (Bull Trout), emphasizing that the relative effectiveness of these different methods varies across species and systems.…”
Section: Snorkel Sampling Versus Electrofi Shingmentioning
confidence: 98%
“…Snorkel sampling has an obvious advantage over electrofi shing because it greatly reduces handling stress and mortality, which is an important consideration when assessing the status of imperiled fi shes (Bohl et al 2009, Jordan et al 2008, Poos et al 2007). Our study indicated that the relative effectiveness of these two methods differed among species and that snorkel sampling was comparable or in some cases superior to electrofi shing for estimating site occupancy.…”
Section: Snorkel Sampling Versus Electrofi Shingmentioning
confidence: 99%
See 2 more Smart Citations